Taguchi method in determining the optimum spot welding parameters for automotive component - Mohd Akram, Che Omar (2008)
Resistance spot welding (RSW) is used for the fabrication of sheet metal assemblies. The process is used widely in the automotive structural application for many years in joining low carbon or "mild" steel. The mild steel also used for the unibody collision repair for the car body [1]. The major advantages of spot welding are high speed and adaptableness for automation in high-volume and/or high-rate production. Despite these advantages, the determination of appropriate welding parameters for spot welding is a very complex matter. A small change of one parameter will influence all the other parameters. For example the different combination value of each of the parameters above will produce the different toughness of weld joining. The welding process is depending on the thickness and the condition of the material to be weld and the kind of the welding apparatus uses [2]. In this study, the Taguchi method is used to determine the optimum spot welding parameters for automotive component, the mild steel or low carbon steel is used in this study. For this study, mild steel with the thickness of 1 mm, 70 mm length and 30mm width will be used as a work pieces. Two work pieces with the same thickness, length and width will be joint using the resistance spot welding. The strength of the joining will be tested using the tensile test machine, an orthogonal array (OA), main effect, single - to - noise (S/N) ratio and analysis of variance (AJslOVA) are applied in order to investigate the optimal spot welding Parameters when different level of parameters are used to weld the work piece. From this study also the main parameters that affect the performance of the spot welding can be determined.